(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The current recommendations for surgery for men with breast cancer (MBC) are heavily influenced by clinical studies with only women as participants. Because there have been no clinical trials for the surgical treatment of MBC, we did a systematic review to compare disease-free survival (DFS), disease-specific survival (DSS), and overall survival (OS) between MBC patients who had breast-conserving surgery (BCS) and those who had a mastectomy. We also looked at radiotherapy compliance among male BCS patients. Objective: The goal of this prospective cohort study is to compare the effectiveness, safety, cost-effectiveness, and cosmetic results of breast conservation surgery (BCS) and mastectomy in treating early-stage breast cancer in developing countries. Material and Method In this prospective cohort study conducted in department of surgery hmc Peshawar from july 2021 t0 july 2022, 100 women with early-stage breast cancer will be randomly given either breast-conserving surgery (BCS) or a mastectomy. The study will be conducted at a single medical center in a developing country. The primary outcome measures will be recurrence-free survival, overall survival, and quality of life. The costs of the two treatments, the cosmetic results, and any side effects will be used as secondary outcome measures. The patients will be followed up for a minimum of 5 years. Results The results of this study will be used to compare the efficacy, safety, cost-effectiveness, and cosmetic outcomes of BCS and mastectomy in the treatment of early-stage breast cancer in developing countries. The primary outcome measure will be recurrence-free survival, overall survival, and quality of life. The costs of the two treatments, the cosmetic results, and any side effects will be used as secondary outcome measures. The patients will be followed up for a minimum of 5 years. Conclusion The results of this study will tell us important things about how well BCS and mastectomy work to treat early-stage breast cancer in developing countries, as well as how safe they are and how much they cost. This information will help doctors in developing countries figure out the best way to treat people with early-stage breast cancer.